Prepubertal Female Bartholin's Gland Abscess: A Comprehensive Case Report Study - Ahmed Salh Alsayed; Tarek Talaat Harb Elkadi; Mohammed Suliman Alshamari; Azza Tawfik Attallah (Hindawi Limited, 2024)
Introduction. Bartholin's gland abscesses are rare in pediatric patients, with limited documented cases. This case report aims to contribute valuable insights into managing this uncommon condition in children. Methods. A thorough examination and diagnostic workup were conducted on a 4-month-old female infant presenting with labial swelling. Clinical assessment strongly suggested the presence of a Bartholin's gland abscess. A culture of purulent discharge revealed the presence of Escherichia coli and Gram-negative Klebsiella pneumoniae. Antibiotic susceptibility testing guided the choice of treatment. Case Presentation. Despite initial treatment with oral antibiotics and sitz baths, there was limited therapeutic response. Close surveillance under the guidance of a pediatric surgeon continued for two months. Subsequently, surgical excision of the Bartholin gland was performed, and the specimen was sent for pathological examination. Results. Pathological analysis revealed signs of ulceration and granulation tissue, indicative of a mixed inflammatory response. An eight-month follow-up demonstrated marked improvement and overall well-being in the patient. Conclusion. This case report underscores the importance of considering Bartholin's gland abscess in diagnosing labial swelling in pediatric patients. The successful outcome achieved through surgical excision and appropriate antibiotic therapy provides valuable insights for potential treatment approaches in similar cases. Continued research and comprehensive studies are essential for establishing optimal treatment protocols for this patient demographic.